Absolute Delusion, Perfect Buddhahood: The Rise and Fall of a Chinese Heresy. Jamie Hubbard. - Barrett, T. H. (Buddhist Studies Review, 2002)
Absolute Delusion, Perfect Buddhahood: The Rise and Fall of a Chinese Heresy. Jamie Hubbard. University of Hawai'i Press, Honolulu 2001. xvii, 333 pp. Hbk $45.00, pbk $22.92. ISBN (pbk) 0-8248-2345-1.